Development of a STEM-Based Circular Motion Module Integrated with the Engineering Design Process - Ramadannisa, Raffa Fitra; Amelia, Nurul Chandra; Rulifiangga, Firda; Widayani, Widayani; Triyanta, Triyanta (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
The low mathematics literacy and science skills of Indonesian students can be caused by among other, the lack of learning media that can improve students’ conceptual understanding, especially in physics. The STEM approach and the Engineering Design Process (EDP) methods can improve problem-solving and creative thinking skills. Therefore, this study aims to develop learning media with the STEM approach and the Engineering Design Process method for Physics subject, namely Circular Motion. The method used in this study is Research and Development with the ADDIE development model, which is limited to: 1) Analysis, 2) Design, 3) Development. The design and development stage involved material and learning experts to test the feasibility of the developed module. The average value of material feasibility of the module is 85.00% with the category “feasible and can be used with minor revisions.” While the average value of learning feasibility is 87.00% with the category “very feasible and can be used without revision”. The result of this study is expected to be the basis for the development of other learning media based on STEM and EDP syntax to improve students’ skills.